Analisis Pertanggungjawaban Pidana Bagi Pelaku Tenaga Pendidik Dalam Melakukan Kejahatan Pencabulan terhadap Anak (Studi Putusan Nomor 75/PID.SUS/2020/PN Metro) - Margaretha Laurinsque L.T; Erna Dewi; Indah Satria (Universitas Batanghari Jambi, 2021)
Fornication embodies the kufr one comes from sexual tyranny which results from the existence of deformations that give birth to a part in the figure of our audience. Fornication is a form of cruelty that plays very sluggishly, especially in the face of the victim, especially if the victim is a child because the child is the future successor or can be called the successor of the nation because sexual immorality will violate human rights and can damage human dignity, especially for the soul, reason and descendants. The problem in this research is what factors influence the criminal act of child molestation and how the accountability is based on Decision Number 75 / Pid.Sus / 2020 / PN Metro. The research method using this research journal is a normative juridical approach and an empirical approach. Based on the results of the research, the factors causing the perpetrator to commit the crime of sexual immorality against this child include religious factors where the faith of the defendant is shaky and tempted by worldly temptations. the occurrence of sexual immorality.